Chemical recycling: A critical assessment of potential process approaches. Issue 10 (October 2022) - Quicker, Peter; Seitz, Mathias; Vogel, Julia
Increased media coverage of plastic pollution in the environment and import bans on plastic waste in several countries have resulted in plastic waste becoming one of the most discussed waste streams in recent years. In the European Union (EU), only about one-third of the post-consumer plastic waste is recycled; the rest goes to energy recovery and landfilling in equal parts. In connection to the necessary increase in efforts to achieve the ambitious EU recycling targets, chemical recycling is currently receiving more and more attention. The assumption is that chemical recycling processes could open up new waste streams for recycling and generate valuable raw materials for the chemical industry. Although there exists no legal definition for chemical recycling, there is more or less agreement that it covers the conversion of plastic polymers into their monomers or chemical building blocks. Techniques such as gasification, pyrolysis and liquefaction as well as solvolysis can be used for chemical recycling. So far, only few large-scale plants for chemical recycling exist worldwide. This article presents the different processes by means of examples from (formerly) running installations and their suitability for plastics recycling is assessed. However, to date, only few chemical recycling plants are in continuous operation, and further scientific evidence for the ecological and economic benefits is still necessary for final evaluation.